(untitled) (Annual of the Faculty of Philosophy in Skopje, 2007)
During the conflict in the Republic o f Macedonia, it was becoming more and more evident that the spiral o f conflict is out of control of the Macedonian security forces. In other words, the scope and the intensity o f the conflict were announcing that the conflict coidd easily bring the Republic o f Macedonia on the edge of civil war with big consequences for the countiy and destabilization o f the wider region. In those conditions, had to be found fast solution between conflict, civil war and auto destruction on one side, or compromised peace on the other side. That is why, Macedonian government askedfor international help and also insisted that the so called third party have transformational role in the conflict. Or, said differently, the third party i.e. international community had active side in the conflict and therefore changed its original matrix and dynamics. The way in which the European Union reacted to the conflict in the Republic o f Macedonia was a test for the developing of new institutional framework o f the Foreign Security and Defence Policy and the political credibility o f the European Union on the international scene. Furthermore, the role of the OSCE in the conflict in the Republic o f Macedonia is seen through the activities undertaken by the Organization in direction to managing the conflict and its ending. Namely, NATO together with the EU, OSCE and the Macedonian side gave their contribution towards undertaking a series o f significant complementary reforms and measures o f confidence with primary aim to support wider political agreements and establish peace.